Selective removal of tin from industrial waste with ion exchange resins - Hagad, Luciana T. (1979)
Ion exchange, the phenomena of trading one ion for another has been employed in the recovery of metals from industrial waste stream. In this study, an ion exchange process is applied for the selective removal of tin metal from industrial waste occurring in scrap tinplates, plating rinse water and sludge. The essence of the process is the use if Dowex SBR-P, a strongly basic anion exchange resin of the trimethyl ammonium polystyrene type for the selective removal of anionic complex tin ions. The resin is readily regenerated with 10% NaCl solution.